Increasing participation through top-level success? Long-term analyses of German, French and Austrian table tennis - Haut, J. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
Associations and policy makers often try to use successful athletes as figureheads who shall inspire more people to participate in a sport. However, former research indicates that success does not trigger mass participation in general, but only may do so in rather specific constellations (De Bosscher et al 2013; Frick and Wicker 2016; Weimar et al 2015). This relation shall be studied for the case of table tennis from an international, comparative perspective. For this purpose, long-term membership figures (since 1960s) of table tennis associations in Germany, France and Austria were collected. Multivariate statistical analyses, including indicators of sport activity and of performances at international championships, are used to measure possible effects of elite success on mass participation. Preliminary analyses suggest partly paradox effects: Only the French case indicates systematic effects in both the Secrétien and Gatien era. In the case of Germany, table tennis grew stronger than other sports after a successful 1969 WTTC at home, but stagnated or decreased - more than other sports - in the even more successful years since 1989. The Austrian case indicates a "Werner Schlager effect", but rather after the "minor" early success (1999 bronze medal) than after the 2003 world championship. Thus it shall be discussed in detail under which conditions and in which way elite success may be a trigger for mass participation in table tennis.